Apoyo contable en la elaboración de la información exógena 2014 Contraloría General del Quindío (2015)
Colombian government is the one in charge of regulating natural people as legal through an administrative entity known as DIAN (Dirección de Impuestos y Aduanas Nacionales). This organization has the target of guaranteeing state fiscal security and protecting the national economical public order by the administration and control to the right accomplishment of duties that are set up in the law. Taking into account what was said before, the general national audit office of Quindio must prepare and represent exogenous information before DIAN; and that is why there is a necessity to carry out the surrender of it, according to the parameters established by law, in its elaboration, application and due date. In this way is presented an opportunity for students to apply their knowledge and to enrich in a practical way the countable thoughts and ideas that were acquired in the university.